Comparative Study of Listening Anxiety and Listening Performance of InHouse Test (TEP) for Female and Male Undergraduate Students - Nadiatus Sholichah; Rahayu Kuswardani (Jurnal Ilmiah Profesi Pendidikan, 2025)
This comparative study investigates gender-based differences in listening anxiety and its relationship with listening performance on the Test of English Proficiency (TEP) among first-year English undergraduates. Listening anxiety, which includes components of Tension and Worry and a Lack of Confidence, is a significant psychological barrier that can negatively impact performance in high-stakes testing environments. The study aims to analyze the differences in listening anxiety and TEP listening scores between male and female students. It also seeks to determine if the strength of the relationship between anxiety and performance differs significantly across genders. A quantitative comparative design was used with 60 first-year English students (23 males, 37 females) from a university in Surabaya. Data were collected using the Foreign Language Listening Anxiety Scale (FLLAS) and students' official TEP listening scores. The analysis involved independent samples t-tests, Pearson correlation, and Fisher’s r-to-z transformation to compare groups and correlation strengths. The findings revealed that female students reported significantly higher overall anxiety (M = 74.05) compared to male students (M = 61.96). This difference was significant across both anxiety sub-factors: Tension and Worry (p = 0.001) and Lack of Confidence (p < 0.001). However, there was no significant gender difference in listening performance scores (Male M = 48.43; Female M = 45.95). A significant negative correlation between anxiety and performance was found for both males (r = –0.666, p = 0.001) and females (r = –0.509, p = 0.001), but the strength of this correlation did not significantly differ between genders. While female students experience greater listening anxiety, its negative impact on test performance is consistent for both genders. The results highlight the need for pedagogical strategies that address both emotional tension and self-confidence to help all students manage anxiety in high-stakes testing situations.